University Autonomy and Academic Freedom: A Commitment to Truth - Joshi, Amma Raj (SCHOLARS: Journal of Arts & Humanities, 2019)
This paper analyzes several aspects of university autonomy, explores the conditions of Nepali universities and suggests what Nepal needs to do to ensure autonomous academic environment at the universities for creation and expansion of knowledge. Based on the reflections of thinkers, educationists and the personal experience of the writer as a faculty at Tribhuvan University of Nepal, I conclude that Nepali universities are under the political and bureaucratic gaze; they are far from becoming the enclaves of free thinkers and knowledge seekers. As a result, academic freedom is doubtful until universities gain autonomous decision-making powers in structural, academic, financial and administrative fronts.